Kajian Literatur: Analisis Metode Alkalisasi Menggunakan NaOH untuk Meningkatkan Gaya Adhesi Antarmuka Serat-Matriks dalam Sintesis Biokomposit - Elok Hidayah; Hilya Wildana Sofia; Ulfiyatul Fitriyah; Faridatul Amanah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Advances in science and technology are faced with a number of challenges, one of which is preserving the environment which is faced with the use of synthetic materials. Synthetic materials are basically materials that cannot be decomposed naturally and pollute the environment. Therefore, a number of research and developments have been carried out in utilizing more environmentally friendly materials through the manufacture of biocomposites. However, the use of biocomposites has not been able to replace the use of synthetic materials as a whole, due to the weak bonding of the fiber-matrix interface (adhesion between fiber and matrix) in biocomposites. One effort that can be made to increase fiber-matrix interfacial bonding in biocomposites is through modification of natural fibers using NaOH. A number of studies have been carried out using NaOH to modify the fiber-matrix surface. The results obtained through a number of studies state that each natural fiber has a different response to NaOH concentration, so that each natural fiber requires a certain concentration to increase the bond between the fiber-matrix interface in biocomposites.